Direito ao esquecimento e condenações penais: outras perspectivas sobre o tema - Maurmo, Julia Gomes Pereira (2017)
The purpose of the present study is to cast a new light on the classic debate involving the apparent conflict between the right to be forgotten and the rights to freedom of expression and to memory, so that other elements can be considered when analyzing the concrete case. In addition to demonstrating the possibility of fulfilling all rights to their maximum extent possible, interdisciplinarity was used in order to evidence the importance of adding to the discussion the perspective of the indispensability of forgetting as a way of ensuring individual health and the dignified life of the citizens. Finally, decisions involving the “Candelária Massacre” and the “Aída Curi Case” were brought to discussion in order to demonstrate that, regarding the right to be forgotten, the inclusion of a perspective concerning health itself not only contributes to fairer decisions, but also provide more objective criteria to the implementation of such right